Multiplex basophil activation tests for allergy diagnosis: present and future applications - Ana Koren; Peter Korosec; Peter Korosec (Frontiers in Allergy)
The basophil activation test (BAT) has become a major cellular in vitro test for evaluating the allergenic activity of specific IgEs. The impact of the BAT is due to the ability of blood basophil granulocytes to present IgE on the high-affinity FcεRI receptor and to mirror the mast cell response that elicits an acute allergic reaction. The BAT proved to be able to identify allergic patients at risk of reacting to a low dose of the allergen and/or developing life-threatening reactions and thus can significantly improve the current management of allergic patients. However, to improve the diagnostic utility for identifying the allergenic activity of different genuinely sensitizing allergens and lower the procedure and labour requirements, developing a multiplex BAT approach incorporating multiple allergen components would be highly anticipated. Recently, the novel multiplex BAT was described utilizing two major innovative steps. The first step was the fluorescent labeling of allergens. The second step was applying fluorescently labeled allergens in flow cytometry assessment to analyze the activation of basophil subpopulations gated according to the binding of different allergens or to evaluate the fluorescence intensity of multiple allergens on the surface of basophils. These novel cellular multiplex approaches will advance our understanding of IgE-mediated responses. Integration of multiplex BAT, in addition to multiplex IgE assays into practice, will personalize the measurement of allergenic IgE activity and can help estimate the likelihood of clinical relevance and risks for multiple allergens when testing individual allergic patients.